Tomographic evaluation of changes induced by herbst treatment - buccolingual inclination of mandibular canines and the intercanine distance - Schwartz, João Paulo; Ravelli, Taisa Boamorte; Ruf, Sabine; Ravelli , Dirceu Barnabé (Acta Scientiarum. Health Sciences, 2023)
The aim of this study was to perform a three-dimensional evaluation of Herbst appliance effects on the mandibular canines.The subjects consisted of 23 Class II:1 patients (12 men, 11 women), mean age of 15.76± 1.75 years, consecutively treated with a Flip-Lock Herbst®appliance (TP Orthodontics, Inc., La Porte, IN, USA). The lower anchorage unit for the Herbst appliance consisted of two anchor bands connected by a lingual arch with 3mm distance from the incisor’s lingual surface. Treatment changes in mandibular canine inclination and mandibular intercanine width at the cusp and apex levels were evaluated by means of cone-beam computed tomography images (i-CAT® Classic unit, Imaging Sciences International, Hatfield, PA, USA) obtained before and after treatment with the Herbst appliance. There were no statistical differences between genders. Herbst appliance treatment did not result in any statistically significant changes for mandibular canine inclination and mandibular intercanine width. There were associations between mandibular canine inclination and mandibular intercanine width at the cusp (/r/ = 0.43 to 0.66) and apex levels (/r/ = 0.34 to 0.60). The three-dimensionalcone-beam computed tomography analysis of the mandibular canine segment revealed that the Herbst appliance with a mandibular anchorage unit distant from the incisor’s lingual surface does not change mandibular canine inclination and mandibular intercanine width significantly during treatment. However, large interindividual differences may result in undesired amount of mandibular canine anchorage loss in individual patients.